ASSESSMENT OF RIGID PAVEMENT CONDITION USING PAVEMENT CONDITION INDEX METHOD ON THE DENAI-MANDALA BYPASS ROAD SECTION IN MEDAN CITY - Aldyoki Firmansyah Matondang; Defry Basrin; Haikal Fajri (Bulletin of Engineering Science, Technology and Industry, 2024)
Road pavement is a critical component of the transportation system that requires maintenance to ensure the pavement remains safe and comfortable for traffic users. Assessing road conditions is crucial for identifying various types of potential damage, thus necessitating specific methods for evaluating road damage conditions. The Pavement Condition Index (PCI) method is commonly used to assess pavement conditions. The aim of this research is to evaluate rigid pavement damage on the Denai-Mandala Bypass road section in Medan City using the Pavement Condition Index (PCI) method. The methodology used in this research involves field surveys for collecting pavement condition data and analyzing the data using the PCI method to determine pavement conditions and types of damage. This research indicates that the rigid pavement on the Denai-Mandala Bypass road section in Medan City experiences various types of damage, including corner break (2 occurrences), divided slab (1 occurrence), durability (“D”) cracking (2 occurrences), faulting (6 occurrences), joint seal damage (10 occurrences), linear cracks (78 occurrences), patching large (11 occurrences), patching small (1 occurrence), polished aggregate (5 occurrences), punchout (2 occurrences), scalling (4 occurrences), shrinkage cracks (10 occurrences), spalling corner (5 occurrences), and spalling joint (30 occurrences). The average PCI value on the Denai road section examined for approximately ±1.4 km is 78.53, categorized as satisfactory with periodic maintenance as the priority for handling, while on the Mandala Bypass road section examined for approximately ±800 m, the average PCI value is 89.93, categorized as very good with routine maintenance as the priority for handling. Assessing pavement conditions using the PCI Method aids in identifying occurring damage and provides necessary information for effective pavement repair planning.